2011
DOI: 10.1371/journal.pone.0021788
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxy-D-Glucose Treatment Induces Ketogenesis, Sustains Mitochondrial Function, and Reduces Pathology in Female Mouse Model of Alzheimer's Disease

Abstract: Previously, we demonstrated that mitochondrial bioenergetic deficits preceded Alzheimer's disease (AD) pathology in the female triple-transgenic AD (3xTgAD) mouse model. In parallel, 3xTgAD mice exhibited elevated expression of ketogenic markers, indicating a compensatory mechanism for energy production in brain. This compensatory response to generate an alternative fuel source was temporary and diminished with disease progression. To determine whether this compensatory alternative fuel system could be sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 58 publications
8
116
0
Order By: Relevance
“…In contrast, in mammalian systems, both glucose and glycerol induce Aβ toxicity [463,527,528]. Interestingly, we also found that 2DOG administration significantly reduced Aβ-mediated paralysis, which is consistent with results in mammalian cell lines and mouse models [31,32]. Understanding this point of contradiction may provide valuable insight into proteotoxicity resulting from hyperglycemia.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In contrast, in mammalian systems, both glucose and glycerol induce Aβ toxicity [463,527,528]. Interestingly, we also found that 2DOG administration significantly reduced Aβ-mediated paralysis, which is consistent with results in mammalian cell lines and mouse models [31,32]. Understanding this point of contradiction may provide valuable insight into proteotoxicity resulting from hyperglycemia.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, MICA was not able to reduce dld-1 gene and protein expression. It has, however, been known to inhibit DLD protein activity and reduce downstream energy metabolism [32,496]. The suppression of dld-1 by RNAi in C. elegans is associated with stress resistance [46,409].…”
Section: Mica Up To 10mm Does Not Alter Dld-1 Gene or Protein Expressionmentioning
confidence: 99%
See 3 more Smart Citations